(untitled) - Bodoor Mohammad Al-Matarneh; Omar Abdulhmeed Al-Khawaldeh; Arwa Mahmoud Alsaraireh (University of Ostrava, 2023)
Aim: To investigate the knowledge, attitudes and practices regarding obstetric danger signs among pregnant women attending antenatal clinics in Jordan. Design: A descriptive cross-sectional. Methods: A convenience sample of 352 pregnant women who attended five antenatal clinics at Al-Karak Governorate in southeast Jordan was recruited. Data were collected using self-reported questionnaire and analyzed using descriptive statistics and inferential statistics. Results: The study findings revealed that (59.1%) of the participants had an inadequate knowledge of obstetric danger signs during pregnancy. In addition, the findings showed that the participants had a positive attitude towards obstetric danger signs. Furthermore, the findings showed that (45.7%) of the participants sought medical care when they experienced obstetric danger signs during pregnancy. The most significant factors affecting the level of knowledge were: age, participant's occupation and the history of stillbirth. Conclusion: The study findings demonstrated that the participants had inadequate knowledge and positive attitudes toward obstetric danger signs during pregnancy. Effective educational programs and other awareness interventions are needed to enhance awareness of obstetric danger signs during pregnancy.